A longitudinal study of the cost of food in Victoria influenced by geography and nutritional quality - Claire Palermo; Julia McCartan; Sue Kleve; Kompal Sinha; Alan Shiell (Australian and New Zealand Journal of Public Health, 2016)
Abstract Objective: To monitor the cost and affordability of a nutritious diet and to assess the influence of distance from the capital city and socioeconomic status on the cost of nutritious food in Victoria. Methods: Twenty‐six of Victoria's 79 local government areas (33%) were randomly chosen for inclusion in the study. A random sample of stores was selected for inclusion from each local government area. The cost of the 44 ‘healthy’ and 10 ‘discretionary’ food and drinks in the healthy food basket for a family of four for a fortnight was collected during the winter and summer of 2012, 2013 and 2014. Results: The mean cost of the basket increased from $424.06 ± 38.22 in winter 2012 to $451.19 ± 33.83 in summer 2014 (p<0.001), representing about 31% of government benefit household income. Fruit and vegetables prices were the most varied over time. Distance of the store from state capital city centre predicted difference in food cost. Conclusions: These findings show that a healthy diet may be unaffordable for some Victorians. Implications: The cost of food is a key factor influencing intake. Public health strategies may need to consider strategies to make healthy food more affordable for some.